Principal's Strategy in Improving Student Discipline at Senior High School 1 Jayapura - Agnes Aryesam; Febi Adriana Mutiara Sogalrey; Agnes Toam (Universitas Negeri Malang, 2025)
Abstract: This study examines the principal's strategy in improving student discipline at SMA Negeri 1 Jayapura, with the aim of understanding the implementation of discipline strategies and the supporting and inhibiting factors that exist. The method used is qualitative research with a descriptive design, which collects data through observation, interviews, and documentation. The subjects of the study consisted of principals and teachers at SMA Negeri 1 Jayapura. The results of the study indicate that the principal's strategy in improving discipline includes several important steps. First, the implementation of clear and integrated rules in the annual program. The principal uses the Student Rules of Conduct Book (TATIBSI) as a guide for school activities that have been recorded and standardized. TATIBSI provides direction regarding school regulations and ensures that each student understands and obeys the rules clearly. The principal provides exemplary examples, especially in terms of neatness of dress and punctuality, which are expected to be role models for students. Second, the regulations are emphasized by dividing the categories of violations from minor to serious. This division helps students understand the level of violation and its consequences better. Third, collaboration between the principal, teachers, and parents in monitoring student discipline is also an important part of this strategy. With good communication between the school and parents, student discipline can be monitored more effectively, both inside and outside the school. Fourth, the principal also applies the “5 S” culture (smile, greet, say hello, be polite, be polite) to create an environment that supports and supports the development of student discipline. This culture helps create a friendly, appreciative, and respectful atmosphere, which contributes to the creation of discipline in everyday life at school. With these strategies, the principal strives to create a more disciplined and productive environment for students. Keywords: Discipline, principal strategy, SMA Negeri 1 Jayapura